Flexural Resistance of Steel-Coconut Shell Concrete-Steel Composite Beam with Normal and J-Hook Shear Studs - Thangasamy, Lakshmi; Kandasamy, Gunasekaran (International Journal of Integrated Engineering, 2020)
Many research on double skin sandwich having top and bottom steel plates and in between concrete core called as steel-concrete-steel (SCS) were carried out by them on this SCS type using with different materials. Yet, use of coconut shell concrete (CSC) as a core material on this SCS form construction and their results are very limited. Study investigated to use j-hook shear studs under flexure in the concept of steel-concrete-steel (SCS) in which the core concrete was CSC. To compare the results of CSC, the conventional concrete (CC) was also considered. To study the effect of quarry dust (QD) in its place of river sand (RS) was also taken. Hence four different mixes two without QD and two with QD both in CC and CSC was considered. The problem statement is to examine about partial and fully composite, moment capacity, deflection and ductility properties of CSC used SCS form of construction. Core concrete strength and the j-hook shear studs used are influences the moment carrying capacity of the SCS beams. Use of QD in its place of RS enhances the strength of concrete produced. Deflections predicted theoretically were compared with experimental results. The SCS beams showed good ductility behavior.